1983
DOI: 10.1097/00000658-198307000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C as an Adjuvant in Resected Gastric Cancer

Abstract: As a result of their previous experience with mitomycin C at high discontinuous doses in advanced gastric cancer, the authors studied its role as an adjuvant for locally advanced cases after surgical complete resection. Results from 70 evaluable patients are presented. Patients were allocated randomly to receive mitomycin C, 20 mg/m2 I.V. direct once every 6 weeks, four courses, or a placebo. After a follow-up period of 250 weeks, seven patients of treatment arm and 23 controls have already relapsed (p less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 2 publications
0
16
0
2
Order By: Relevance
“…In these patients, it is questionable whether or not curative surgery had been conducted, and it seems to be difficult to achieve positive results with postoperative adjuvant chemotherapy in these patients with a poor prognosis. In 1983, Alcobendas et al [39] reported on a trial that compared treatment with MMC to observation alone after surgery. Although there was a significant survival advantage for treatment with MMC, the number of patients was very small and the follow-up …”
Section: Western Postoperative Adjuvant Chemotherapy Trialsmentioning
confidence: 99%
“…In these patients, it is questionable whether or not curative surgery had been conducted, and it seems to be difficult to achieve positive results with postoperative adjuvant chemotherapy in these patients with a poor prognosis. In 1983, Alcobendas et al [39] reported on a trial that compared treatment with MMC to observation alone after surgery. Although there was a significant survival advantage for treatment with MMC, the number of patients was very small and the follow-up …”
Section: Western Postoperative Adjuvant Chemotherapy Trialsmentioning
confidence: 99%
“…No attempt was made to identify ongoing trials with unpublished results. For studies published more than once during follow-up, only the last: nal version, or the one presenting the most detailed results, have been included (24)(25)(26)(27)(28)(29)(30)(31). Two studies included in the earlier meta-analysis (23), one using immuno-therapy and the other only published in Japanese, were excluded in this analysis.…”
Section: Comments On the Included Studiesmentioning
confidence: 99%
“…The majority of them gives no details on the procedure (Harrisson et al, 1989;Tonnesen et al, 1988;Moertel et al, 1984;Engstrom et al, 1985;Hugier et al, 1980;Nakajima et al, 1978;Nakajima et al, 1980;Maehara et al, 1990;Schlag, 1987;Lise et al, 1989;Allum et al, 1989c;Koyama et al, 1986;Higgins et al, 1983;Popiela et al, 1988;GITSG, 1982;Blake et al, 1981;Alcobendas et al, 1983) some lay down guidelines for surgical procedure (Coombes et al, 1990;Ochiai et al, 1983;Serlin et al, 1969;GITSG, 1982;IGTSG, 1988) or recommend a specific type of resection (Allum et al, 1989b). None had organised a pathological review of all operative specimens (Coombes et al, 1990).…”
mentioning
confidence: 99%
“…Among the six trials showing a benefit on survival in favour of the investigational treatment, two were testing chemotherapy agents (Alcobendas et al, 1983;GITSG, 1982), three immunotherapy (Ochiai et al, 1983;Koyama et al, 1986;Youn et al, 1989) and one the histamine-2-receptor antagonist cimetidine.…”
mentioning
confidence: 99%
See 1 more Smart Citation